Trust based security model for cloud systems in an organization - Rahmani, Mohammad Saalem; Al-Hussaini, AbulFathi Ibrahim Saleh; Ibrahim, Adamu Abubakar (IIUM Press, 2021)
Cloud storage has several advantages and benefits, including cost savings, increased adaptability, elasticity, and resource efficiency. For all of these advantages, there are also drawbacks and concerns for cloud users. The dispersed and opaque nature of cloud computing services creates several difficulties in their utilisation. As a result, users have little control over their data and information and are unclear if they can trust cloud providers. Consequently, the purpose of this research is to investigate the impact of customer and provider characteristics on cloud service outcomes, as well as the impact of trust on cloud service outcomes, and to see if trust mediates the relationship between customer and provider characteristics and cloud service outcomes. In order to fulfil the study's objectives, the measurement model, factor analysis, structural model assessment, and regression analysis were analysed. According to the study's findings, existing threats in cloud services are one of the reasons customers do not trust cloud service providers. Cloud services are unattractive because of the threats to privacy and security. This study also revealed that trust is critical for cloud service users and providers since it promotes utilisation, customer desire to use, and cloud service provider reputation. It was also observed that if there is no trust in these programmes, the results are quite bad. This research can help cloud service providers/developers understand why some individuals and organisations are unable to use their services.